Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1152/japplphysiol.00516.2014
|View full text |Cite
|
Sign up to set email alerts
|

Muscle sympathetic nerve activity during cold stress and isometric exercise in healthy older adults

Abstract: Greaney JL, Stanhewicz AE, Kenney WL, Alexander LM. Muscle sympathetic nerve activity during cold stress and isometric exercise in healthy older adults. J Appl Physiol 117: 648 -657, 2014. First published August 7, 2014 doi:10.1152/japplphysiol.00516.2014.-Cardiovascular mortality increases in cold weather in older adults, and physical activity may impart even greater cardiovascular risk than cold exposure alone. Human aging is associated with exaggerated pressor responses to whole body cooling; however, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 64 publications
6
47
0
Order By: Relevance
“…Whole-body cooling-induced decreases in mean skin temperature elicit a pronounced systemic pressor response in healthy young adults (Cui et al, 2007; Cui et al, 2005b; Durand et al, 2004; Greaney et al, 2014; Hess et al, 2009; Wilson et al, 2007); a similar pressor response also occurs during more severe cold stress during which reductions in core temperature are observed (Collins et al, 1985; Inoue et al, 1992; Wagner et al, 1985). The pressor response to cooling is likely mediated by increases in sympathetic activation, because skin surface cooling increases total peripheral resistance without altering cardiac output (Cui et al, 2005b; Durand et al, 2004; Raven et al, 1980).…”
Section: Sympathetic Regulation During Cold Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…Whole-body cooling-induced decreases in mean skin temperature elicit a pronounced systemic pressor response in healthy young adults (Cui et al, 2007; Cui et al, 2005b; Durand et al, 2004; Greaney et al, 2014; Hess et al, 2009; Wilson et al, 2007); a similar pressor response also occurs during more severe cold stress during which reductions in core temperature are observed (Collins et al, 1985; Inoue et al, 1992; Wagner et al, 1985). The pressor response to cooling is likely mediated by increases in sympathetic activation, because skin surface cooling increases total peripheral resistance without altering cardiac output (Cui et al, 2005b; Durand et al, 2004; Raven et al, 1980).…”
Section: Sympathetic Regulation During Cold Stressmentioning
confidence: 99%
“…Further, cold stress increases indirect indices of sympathetic nervous system activation (e.g., plasma NE) in young adults (Durand et al, 2004; Frank et al, 2000). Interestingly, findings from studies employing direct measures of MSNA during whole-body cooling in young adults are equivocal (Cui et al, 2007; Fagius et al, 1991; Greaney et al, 2014). For example, studies in which skin surface cooling was induced via a water-perfused suit (to decrease mean skin temperature from a thermoneutral of ~34 to ~30°C and without any reduction in core temperature) reported no change in MSNA during cold exposure (Cui et al, 2007; Greaney et al, 2014).…”
Section: Sympathetic Regulation During Cold Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Recordings of efferent discharges in the postganglionic sympathetic C efferent fibers innervating muscle and skin provide direct information about muscle sympathetic nerve activity (MSNA) and SSNA. A number of studies have employed microneurography to measure the total muscle and/or skin sympathetic nerve activity in response to stress (Mano, 1997;Middlekauff et al, 2002;Greaney et al, 2014). MSNA is recorded by penetrating the electrode tip in the muscle nerve fascicles, while SSNA is recorded from the skin nerve fascicles.…”
Section: Muscle And/or Skin Sympathetic Nerve Activity (Microneurogramentioning
confidence: 99%
“…Furthermore, studies have reported a blunted rise in blood pressure after a spontaneous burst of MSNA in older adults (140,153), suggesting potential age-related impairments in sympathetic vascular transduction to resistance arterioles. Thus age-related changes in the ability of MSNA to modulate vascular tone may contribute to altered blood pressure regulation during cold stress in older adults (61,68,157); however, this requires further study to extrapolate these findings to the skin circulation.…”
Section: Postjunctional and Vessel Responsesmentioning
confidence: 99%